Fostering Healthier Choices: Empowering Pharmacy Students to Bridge the Food Label Gap in Lebanon - Sonji, Nada M.; Sonji, Ghassan M. (Jordan Journal of Pharmaceutical Sciences, 2024)
Background: Non-communicable diseases are a significant public health issue in Lebanon, making it crucial to promote preventive measures such as informed dietary choices. Food labels play a key role in this, but there is a disconnect between knowledge and utilization, even among healthcare professionals. This study aimed to investigate this gap among Lebanese pharmacy students by assessing their nutrition knowledge, usage of food labels, and the factors influencing their label use. Materials and Methods: This cross-sectional study examined the knowledge gap among 81 pharmacy students in Beirut. A validated questionnaire assessed demographics, nutrition knowledge, label features influencing purchase decisions, and barriers to label use. Results: Despite having high overall nutrition knowledge (mean score of 82%), students reported inconsistent use of food labels. Gender did not significantly influence the prioritization of label features. However, students in higher academic years were more likely to pay attention to production dates (p < 0.001). Additionally, there was a positive correlation between the frequency of label use and knowledge scores. Conclusion: This study highlights a persistent knowledge-practice gap in food label utilization among pharmacy students. Educational interventions tailored to address specific knowledge gaps and perceived barriers are necessary.